2002
DOI: 10.1074/jbc.m206130200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Complex Formed between a Snake Venom Phospholipase A2 and a Potent Peptide Inhibitor Phe-Leu-Ser-Tyr-Lys at 1.8 Å Resolution

Abstract: Phospholipase A 2 is an important enzyme involved in the production of prostaglandins and their related compounds causing inflammatory disorders. Among the several peptides tested, the peptide Phe-Leu-Ser-Tyr-Lys (FLSYK) showed the highest inhibition. The dissociation constant (K d ) for this peptide was calculated to be 3.57 ؎ 0.05 ؋ 10 ؊9 M. In order to further improve the degree of inhibition of phospholipase A 2 , a complex between Russells viper snake venom phospholipase A 2 and a peptide inhibitor FLSYK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…There have also been extensive investigations to understand their (www.interscience.wiley.com) DOI:10.1002/jmr.960 catalytic actions and various ligands have also been designed to inhibit their enzymatic function. The structures of several complexes of PLA 2 with natural compounds (Chandra et al, 2002a(Chandra et al, , 2002dSingh et al, 2006a), substrate analogues (Scott et al, 1990;Thunnissen et al, 1990;Scott et al, 1991;Sekar et al, 1997;Epstein et al, 2001;Pan et al, 2001;Hansford et al, 2003) and with other designed synthetic compounds (Schevitz et al, 1995;Chandra et al, 2002bChandra et al, , 2002cSingh et al, 2003) have also been reported. The anti-inflammatory response of non-steroidal anti-inflammatory drugs (NSAIDs) has been attributed to their binding to PLA 2 (Singh et al, , 2006bJabeen et al, 2005) and COX enzymes Gierse et al, 1999).…”
mentioning
confidence: 98%
“…There have also been extensive investigations to understand their (www.interscience.wiley.com) DOI:10.1002/jmr.960 catalytic actions and various ligands have also been designed to inhibit their enzymatic function. The structures of several complexes of PLA 2 with natural compounds (Chandra et al, 2002a(Chandra et al, , 2002dSingh et al, 2006a), substrate analogues (Scott et al, 1990;Thunnissen et al, 1990;Scott et al, 1991;Sekar et al, 1997;Epstein et al, 2001;Pan et al, 2001;Hansford et al, 2003) and with other designed synthetic compounds (Schevitz et al, 1995;Chandra et al, 2002bChandra et al, , 2002cSingh et al, 2003) have also been reported. The anti-inflammatory response of non-steroidal anti-inflammatory drugs (NSAIDs) has been attributed to their binding to PLA 2 (Singh et al, , 2006bJabeen et al, 2005) and COX enzymes Gierse et al, 1999).…”
mentioning
confidence: 98%
“…Apart from a large number of van der Waals interactions, the peptide ligand (P) makes hydrogen bonds with certain residues in the channel. The hydrogen bonded interactions include Ser10 O␥· · ·Ala(P1) In the same study, it has been established that a peptide inhibitor consisting of hydrophobic residues and a basic residue at the C-terminus is an ideal design of a PLA 2 inhibitor [37]. Therefore the native peptide inhibition analysis in this study is totally in accordance with the crystal structure data.…”
Section: Connecting Peptide As a Reversible Inhibitor Of The Enzymatimentioning
confidence: 50%
“…This type of pentapeptide is reminiscent of native derived pentapeptides that have been shown to effectively inhibit PLA 2 [36,37]. With this background we sought to explain the necessity of the pentapeptide in the MtsPLA 2 .…”
Section: Connecting Peptide As a Reversible Inhibitor Of The Enzymatimentioning
confidence: 99%
“…The structures of several complexes of PLA 2 with natural compounds [29][30][31], substrate analogues [17,32], indole derivatives [37][38], non-steroidal anti-inflammatory drugs (NSAIDs) [33][34][35] and with designed peptides [39][40] have been investigated. The substrate-binding site in PLA 2 is a part of the hydrophobic channel.…”
Section: Enzyme-inhibitor Complexesmentioning
confidence: 99%
“…Several structures of PLA 2 complexes with natural compounds [29][30][31], substrate analogues [17,32], nonsteroidal anti-inflammatory drugs (NSAIDs) [33][34][35] and other designed synthetic compounds including peptides [36,[39][40] have been reported. These studies have led to a complete identification of the structural elements of ligand recognition in the hydrophobic channel of PLA 2 , thus paving the way to further improving the quality of inhibitors using structure-based design approach.…”
Section: Introductionmentioning
confidence: 99%